Effects and Mechanism of Different Phospholipid Diets on Ovary Development in Female Broodstock Pacific White Shrimp, Litopenaeus vannamei - Liang, Xiaolong; Luo, Xiaolong; Lin, Hongxing; Han, Fenglu; Qin, Jian G.; Chen, Liqiao; Xu, Chang; Li, Erchao (Frontiers in Nutrition, 2022)
Research on nutrition and feed development for the broodstock of the Pacific white shrimp, Litopenaeus vannamei is rare, and poor broodstock quality is a critical factor restricting seed supply in shrimp farming. As an essential nutrient for the gonadal development of L. vannamei, one control diet (no phospholipid) and three typical phospholipids (soybean lecithin, egg yolk lecithin and krill oil) were evaluated in a semipurified diet with 4% phospholipid for a 28-day trial (initial weight 34.7 ± 4.2 g). Dietary phospholipid supplementation significantly promoted ovarian maturation of female L. vannamei. Compared with soybean lecithin and egg yolk lecithin, krill oil showed the best positive results. Shrimp fed a diet with krill oil obtained a significantly higher gonadosomatic index, yolk particle deposition, lipid accumulation, and estrogen secretion than the other sources. Ovary lipidomic analysis showed that krill oil enriched the lipid composition of the ovary. The “glycerophospholipid metabolism” and “sphingolipid metabolism” pathways significantly varied via topological pathway analysis. Genes and hub genes with significantly different expression levels were significantly enriched in the “fatty acid metabolism pathway”, “glycerophospholipid metabolism” and “arachidonic acid metabolism” pathways by transcriptomic analysis. Correlation analysis of the transcriptome and lipidomics showed that the differential gene “HSL” was positively correlated with various lipids (TG, PA, PS, PE, GlcCer, PG, PI) but negatively correlated with DG, LPE and SM. In conclusion, dietary phospholipids, especially krill oil as a phospholipid source, can promote the development of L. vannamei ovaries by increasing the accumulation of nutrients such as triglycerides and sterols and the secretion of estrogen or related hormones, such as estradiol and methylfarneside, by affecting the metabolism of glycerol phospholipids and some key fatty acids.